Permaculture: A Key Driver for Sustainable Agriculture in Nepal - Bhandari, Devashish; Bista, Bishal (International Journal of Applied Sciences and Biotechnology, 2019)
Our study primarily focused on permaculture for sustained agriculture. Permaculture can be a best alternative for modern industrial and commercial based agriculture which has given a good yield at present but, it is deteriorating soil quality and other environmental aspects. More ever it can lead to a global threat in the future due to overuse and somewhere due to unutilized resources which may give rise to the food and economic insecurity. By compiling the different literatures, we reviewed that permaculture enriches soil quality by increasing organic matter in soil thus increasing water retention capacity, infiltration, nutrient availability, microbial activities and decreasing the erosion. Thus, it increases physical, chemical and biological properties of soil. It provides food and economic safety by providing diverse crops, increasing yield and income of farm and providing least cost inputs with increasing output. It is an efficient in terms of resource use as it utilizes renewable resources and makes connections like a web among resources. This review can be useful information for students, research topic for permaculturists for making it smoother and other environmental enthusiast. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 167-173